Ethical Criteria in Marketing Research - Vaitkūnienė, Živilė (Ekonomika, 2002)
here are many different ethical theories that have been developed over the years by a number of philosophers. An overview of these theories, their strengths and weaknesses and how they can be applied by a marketing researcher to make decisions are presented in this paper. While the above theories all have pros and cons, ethical decision-making models, which are descriptive in nature, come into play. A few leading ethical decision-making models are presented, laying the foundation for a descriptive model for ethics in marketing research, that is developed further. The proposed theoretical model is backed up with an empirical example of marketing research.